Expression of semaphorin class 3 is higher in the proliferative phase on the human endometrium - Ferreira, Gustavo Dias; Capp, Edison; Jauckus, Julia; Strowitzki, Thomas; Germeyer, Ariane (Archives of gynecology and obstetrics, 2018)
Purpose: The semaphorins are related to angiogenesis and cell proliferation depending on the tissue. The purpose of this study was to assess gene expression of class 3 semaphorin (SEMA3A-F) and protein expression of semaphorin 3A (SEMA3A) within human endometrium throughout the menstrual cycle. Methods: Gene expression of SEMA3A-F was analyzed by real-time PCR (qRT-PCR) and protein expression of SEMA3A was analyzed by ELISA in endometrial biopsies in the proliferative and secretory phase of the menstrual cycle. Results: Gene expression of SEMA3A, SEMA3C, SEMA3D, and SEMA3E was statistically significant decreased in secretory compared to proliferative phase endometrium (p < 0.05). Accordingly, SEMA3A protein expression in the secretory phase was lower than protein expression in proliferative phase endometrium (p ≤ 0.05). Conclusion: SEMA3A, 3C, 3D, and 3E are possibly related to cell proliferation in the endometrium, being more expressed in the proliferative phase of the cycle. This finding may stimulate studies of class 3 semaphorins as a possible target for treatment of endometrial pathologies.
Gesehen am 19.05.2020